A Study on Sexual Assault Victims and Associated Factors at a Tertiary Care Centre of a North-Eastern State of India: A Retrospective Study - Mahanta, P; Barman, N; Devi , J; Das, A; Das , M; Gogoi , A (Journal of Indian Academy of Forensic Medicine, 2024)
Sexual assault is a significant crime worldwide, irrespective of different cultures and religions. Most cases are unreported, yet it is a common, frequent and vital public health issue in developed and developing countries. Medico-legal examinations play an important role in determining the clinical and circumstantial evidence against this heinous crime, which helps appropriately present the incident before the courts of Law. This present paper aims to evaluate the socio-demographic profile of the alleged sexual assault victims and the medico- legal characteristics of the event and determine the factors affecting those incidents. A hospital record-based retrospective study was conducted on all the alleged sexual assault victims. Strict confidentiality was obtained in managing data extracted for the study from the hospital records. The ethical clearance was obtained. A gradual rise in the frequency of cases of sexual assault is noticed every year. Age- wise distribution showed that 69.1% of cases were in the age group of 11-20 years. Out of 835 victims, the majority, 89.8%, were Hindus, and 85.4% cases were unmarried. Accused relatives’ houses were the most common place of the incident (31.1%). Most of the alleged victim girls (63.4%) reported having eloped with their boyfriends. Among the victims, 30% reported being force applied, while almost 2% said getting molested. Old hymenal tears were found in most cases (138/267). Sexual assault has lots of risk factors that affect the victim’s physical and interpersonal relationships adversely. Hence, the associated influential factors should be considered to initiate preventive measures and control this sensitive public health issue.